Constructing Dense SiOx@Carbon Nanotubes versus Spinel Cathode for Advanced High‐Energy Lithium‐Ion Batteries. Issue 5 (24th February 2017) - Ming, Hai; Qiu, Jingyi; Zhang, Songtong; Li, Meng; Zhu, Xiayu; Wang, Liming; Ming, Jun
Abstract: A newly designed dense SiO x @carbon nanotubes (CNTs) composite with a high conductivity of 3.5 S cm −1 and tap density of 1.13 g cm −3 was prepared, in which the CNTs were stripped by physical energy crushing and then coated on SiO x nanoparticles. The composite exhibits high capacities of 835 and 687 mAh g −1 at current densities of 100 and 200 mA g −1, which can be finely persevered over 100 cycles. Benefiting from this promising anode, two new full cells of SiO x @CNTs/LiMn2 O4 and SiO x @CNTs/LiNi0.5 Mn1.5 O4 with high energy densities of 2273 and 2747 Wh kganode −1 (i. e. 413 and 500 Wh kgcathode −1 ), respectively, were successfully assembled and can cycle more than 400 cycles. Even with further cycling at the elevated temperature of 45 °C, the cells can still deliver relatively high capacities of 568 and 465 mAh ganode −1, respectively, over 100 cycles. Such desired high‐energy lithium‐ion batteries with working voltages over 4.0 V can be widely developed for diverse applications (e. g. in handheld devices, electric vehicles, and hybrid electric vehicles). The easy extension of the presented synthetic strategy and the configuration of high‐energy battery system would be significant in materials synthesis and energy‐storage devices. Abstract : Under construction : A SiO x @CNTs nanocomposite with high conductivity and tap density is prepared. This nanocomposite can deliver an enhanced capacity with a robust rate capability. Advanced lithium−ion batteries are assembled by using SiO x @CNTs/LiNi x Mn2− x O4 with high working voltages and energy densities.